(untitled) (Academia Science Repository, 2023)
The solution to the problem of developing modern technology and equipment for the production of flour confectionery is to save material resources when creating equipment and in the production of products. Rheology plays an important role in solving this problem, allowing you to create resource-saving technologies and equipment designs. In this paper, theoretical and practical issues related to the processes of mechanical processing of dough for national flour products with stuffing, taking into account its rheological properties, are considered.